Free phenolic compounds in waters of the Ross Sea - Roberta Zangrando; Fabiana Corami; Elena Barbaro; Anna Grosso; Carlo Barbante; Clara Turetta; Gabriele Capodaglio; Andrea Gambaro (Science of The Total Environment, 2019)
The presence of free phenolic compounds (PC) in Antarctic sea water has been investigated to explain their source and particle size distribution in the atmospheric aerosols, as determined in our previous research. The sea water samples were filtered to distinguish the PC concentrations in the particulate and dissolved fractions. Two sample preparation procedures were developed to quantify nine PC in both fractions. The highest concentrations were found in the dissolved fraction of Ross Sea water, with vanillin, vanillic acid, acetovanillone and p-coumaric acid being the most abundant PC. Dissolved PCwere mainly found in the upper part ofwater column. This facilitated the sea water-air exchange by bubble busting processes. In the aerosol, they were mainly found in the fine fraction, where these compounds have a higher degree of oxidation than PC detected in seawater, suggesting that theywere newly emitted and they have been not yet oxidized. These results supported our previous hypothesis that PC were locally emitted into the atmosphere from the Ross Sea. Three different possible sources of PC are hypothesized for Antarctic seawaters: 1) fromthe intrusion ofModified Circumpolar DeepWater that may transport oceanic lignin; 2) fromphytoplankton biomass that may be a source of PC in Antarctic waters since diatoms produce exudates that contain vanillic acid, p-coumaric acid and syringic acid; 3) fromthe melting of glaciers and sea ice: glaciers contain lignin that can be degraded, while in the sea ice there are diatoms that may release PC. Statistical analysis and the low value of vanillic acid/vanillin ratio indicated that the most plausible source for PC in the dissolved fraction was the senescence of phytoplankton. As a contrast, particulate PC with higher vanillic acid/vanillin ratios were ascribed to degraded lignin or the sorption of diagenically oxidized material on particles.